What Are the Ethical Principles of AI in Healthcare? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, offering unprecedented opportunities to improve diagnostics, personalize treat...
Keywords: AI Ethics in Healthcare; Ethical; Principles; Healthcare; Artificial Intelligence; Deep Learning; Digital Health